Myelodysplastic syndrome and immunotherapy novel to next in-line treatments - Katherine Linder; Premal Lulla (Taylor & Francis Group, 2021)
Patients with Myelodysplastic syndromes (MDS) have few therapy options for sustainable responses in the frontline setting, and even less after hypomethylating agent (HMA) failure in relapsed and refractory setting. The only potential cure is an allogeneic hematopoietic stem cell transplant which is an unrealistic option for the majority of MDS patients. Immunotherapy with checkpoint inhibition, CAR-T cells, and vaccine therapy few have shown promise in a variety cancer and have now been tested in patients with MDS. Most trials have focused on AML patients and included small numbers of MDS patients. Until now, a dedicated review of immunotherapy outcomes in MDS patients has been lacking. Thus, herein we review outcomes of MDS patients after immunotherapies on a variety of clinical trials reported to date.